Die Akten des Kaiserlichen Reichshofrats (RHR) - Serie I Alte Prager Akten Band 2: E-J : - Sellert, Wolfgang (2019)
The Aulic Council is one of the most outstanding European supreme courts of its time and one of the most important institutions of the Holy Roman Empire of the German Nation in the early modern period (16th-18th century). In close proximity to the emperor, it dealt with legal disputes and fiefdom, privilege matters and the requests of individuals for help, protection and mediation. The systematic and detailed listing of the records of the Aulic Council preserved in the Austrian State Archives in Vienna provides a comprehensive insight into the tasks of maintaining legal peace with which the Aulic Council had to deal. The records cover not only politically highly explosive conflicts over rule, denomination and territories between the powerful of the Empire; they also make visible everyday disputes over debts, inheritances and provisioning, which were brought before the emperor by nobles and commoners, clergy and laymen, women and men from the entire Empire. The record thus becomes a productive aid both for legal and constitutional history and for the entire intellectual and cultural history of the Old Empire and Europe.